The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.celrep.2016.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Dual Shp2 and Pten Deficiencies Promote Non-alcoholic Steatohepatitis and Genesis of Liver Tumor-Initiating Cells

Abstract: SUMMARY The complexity of liver tumorigenesis is underscored by the recently observed anti-oncogenic effects of oncoproteins, although the mechanisms are unclear. Shp2/Ptpn11 is a proto-oncogene in hematopoietic cells, and antagonizes the effect of tumor suppressor Pten in leukemogenesis. In contrast, we show here cooperative functions of Shp2 and Pten in suppressing hepatocarcinogenesis. Ablating both Shp2 and Pten in hepatocytes induced early-onset non-alcoholic steatohepatitis (NASH), and promoted genesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 54 publications
4
34
2
Order By: Relevance
“…Both of SHP-1 and SHP-2 govern a host of cellular functions with similar or parallel signal pathways (10). Previous studies reported that SHP-2 suppresses tumorigenesis, but promotes the progression of HCC, suggesting that SHP-2 plays bidirectional roles in HCC (47). However, our present data demonstrate that SHP-1 acted as a suppressor in initiation and progression of HCC in mice.…”
Section: Discussioncontrasting
confidence: 75%
“…Both of SHP-1 and SHP-2 govern a host of cellular functions with similar or parallel signal pathways (10). Previous studies reported that SHP-2 suppresses tumorigenesis, but promotes the progression of HCC, suggesting that SHP-2 plays bidirectional roles in HCC (47). However, our present data demonstrate that SHP-1 acted as a suppressor in initiation and progression of HCC in mice.…”
Section: Discussioncontrasting
confidence: 75%
“…The effects of TAZ on inflammation were recently implicated in the progression of NASH (44). Luo et al suggested that the liver microenvironment is a key factor for NASH-derived cancer development in Pten and Shp2 DKO mice (45). Here, we found that the increased levels of TAZ in DKO livers were associated with enhanced immune cell infiltration and increased levels of inflammatory cytokines in the liver ( Figure 1D, Figure 2G, and Table 1), as well as with the rapid development of NASH.…”
Section: Generation Of Liversupporting
confidence: 67%
“…Immunostaining demonstrated significant decrease of CD44v6 + , SOX9 + , EpCam + and V6 + cell numbers in Pten Δ H and DEN-treated Shp2 Δ H liver sections 7 days following pIC treatment (Figure S7H–L). These markers have been previously shown to be associated with liver TICs by a number of groups (Liu et al, 2016; Luo et al, 2016; Yamashita and Wang, 2013). Of note, pIC injection did not cause severe hepatotoxicity, as reflected by serum ALT levels (Figure S7M).…”
Section: Resultsmentioning
confidence: 96%